2001
DOI: 10.1093/nar/29.2.515
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic action of Six3 and Prox1 at the gamma-crystallin promoter

Abstract: Gamma-crystallin genes are specifically expressed in the eye lens. Their promoters constitute excellent models to analyse tissue-specific gene expression. We investigated murine CRYGE/f promoters of different length in lens epithelial cell lines. The most active fragment extends from position -219 to +37. Computer analysis predicts homeodomain and paired-domain binding sites for all rodent CRYGD/e/f core promoters. As examples, we analysed the effects of Prox1 and Six3, which are considered important transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 49 publications
2
42
0
Order By: Relevance
“…2 Reciprocally, phosphorylated ERK is expressed throughout the proliferative population of epithelial cells in neonatal rat lens, extending into the transitional zone (28). Although it is known that several transcriptional factors such as Pax6, Sox2, and Six3 also regulate the expression of crystallin gene (13,34,35), L-Maf is the first example of a differentiation factor that can be regulated directly by FGF signaling in lens development.…”
Section: Discussionmentioning
confidence: 99%
“…2 Reciprocally, phosphorylated ERK is expressed throughout the proliferative population of epithelial cells in neonatal rat lens, extending into the transitional zone (28). Although it is known that several transcriptional factors such as Pax6, Sox2, and Six3 also regulate the expression of crystallin gene (13,34,35), L-Maf is the first example of a differentiation factor that can be regulated directly by FGF signaling in lens development.…”
Section: Discussionmentioning
confidence: 99%
“…Prox1 Activates the Chicken ␤B1-Crystallin Promoter-The vertebrate homolog of Drosophila Prospero, Prox1, is crucial for lens fiber cell elongation (14) and is able to activate ␥-crystallin promoters in transfection assays (16). To test whether Prox1 is also capable of activating the chicken ␤B1-crystallin promoter, co-transfection assays were performed with a Prox1 expression vector in N/N 1003A cells.…”
Section: Pl1 and Pl2 Elements Are Essential For Chicken ␤B1-crys-mentioning
confidence: 99%
“…Prox1 null lenses do not undergo lens fiber cell elongation, although the expression of several fiber cell-specific genes can be detected by RT-PCR (14). In co-transfection assays, Prox1 activates several ␥-crystallin promoters (16). However, it has not been established whether Prox1 is a DNA binding transcription factor like its Drosophila homolog, Prospero (17,18).…”
mentioning
confidence: 99%
“…Although misexpression of Six3 in the medaka converts otic vesicles into lens cells, as evidenced by the expression of crystallin-expressing lens-like structures (Oliver et al, 1996), similar results have not been reported in any other species to date. In mice, Six3 has been found to repress γ-crystallin promoter activity when assayed in N/N1003A and CD5A cells (Lengler et al, 2001). A recent report demonstrates that gain of Six3 function in lens primordium by in ovo electroporation of chick embryos causes an arrest of lens placode invagination and suppresses lens fiber differentiation (Zhu et al, 2002).…”
Section: Six3 In Placode Formationmentioning
confidence: 99%
“…Using cell lines, Prox1 was shown to activate γ-crystallin expression through the responsive element located between nt-151 and nt-174 of the gene promoter (Lengler et al, 2001), suggesting that Prox1 may exert some regulatory effects on later expressed crystallins, including β-crystallin, in the chick.…”
mentioning
confidence: 99%